PENGARUH DENDA PAJAK KENDARAAN BERMOTOR TERHADAP PERILAKU TAAT PAJAK - sabinus, sabinus (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2020)
The present research was conducted to the motor taxpayers in Bengkayang Regency. The research was conducted due to the considerable tax delinquence data in West Kalimantan, which amounted to 920 billion rupiahs that affected the potential for the original revenue of West Kalimantan Province. It needs attention of all stakeholders not to continue. It can affect the provincial original revenue (PAD) of West Kalimantan. The research aimed to determine the government's efforts in improving the realization of payment of motor vehicle taxes and to investigate the extent to which fines affected tax-abiding behavior. The benefits of this research were to provide recommendations how to formulate, evaluate and create tax-abiding automobile vehicles. The present research was quantitative The instruments were lists of interviews and questionnaire. The results showed that the need of administrative sanctions (fines) delayed the payment of motor vehicle taxes. The payment of the fine must not imposed on the running year; it must be paid on the following year. Another finding was that there must be an innovation system notification/Notification of the Samsat/Bapenda online to the taxpayer through a direct billing. Keywords: Motor Vehicle Tax, Behavior, Local Indigenous Revenue